1996
DOI: 10.1093/ageing/25.6.443
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of White Matter Low Attenuation on Cognitive Performance in Dementia of the Alzheimer Type

Abstract: The effect of leukoaraiosis or white matter low attenuation (WMLA) on cognitive function is not fully understood. We compared the neuropsychological performance of 37 Alzheimer's disease patients with WMLA on CT brain scans with a similar group of 31 Alzheimer's disease patients with no evidence of white matter lesions. Patients with WMLA performed significantly worse on tests of visuospatial function (Cube Analysis test, p = 0.004), and cognitive speed (Kenrick Digit Copying test, p = 0.05) compared to those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…Seven normal controls had incomplete batteries, and 8 of the 171 individuals with cognitive impairment either refused or were unable to complete one or more of the Boston naming, 3 Benton line orientation, 5 FAS fluency, 2 and digit span 3 tests. Six of these had probable AD and 2 had probable VaD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven normal controls had incomplete batteries, and 8 of the 171 individuals with cognitive impairment either refused or were unable to complete one or more of the Boston naming, 3 Benton line orientation, 5 FAS fluency, 2 and digit span 3 tests. Six of these had probable AD and 2 had probable VaD.…”
Section: Resultsmentioning
confidence: 99%
“…In otherwise healthy elderly individuals, those with global atrophy and WMHI often show reduced speed of information processing and impaired executive function compared with those with neither atrophy nor WMHI. 3,4 Those with AD and WMHI show greater visuospatial dysfunction, 5 attention/concentration impairment, 6 slower cognitive processing, and greater executive dysfunction 6 than those with AD alone, but other studies find no neuropsychological differences between these 2 groups. [7][8][9] Functional imaging studies show different activation patterns in those with and without WMHI, suggesting that an equivalent level of cognitive impairment results from different mechanisms in AD with and without WMHI.…”
mentioning
confidence: 95%
“…In patients with Alzheimer's disease, widespread white matter lesions were associated with poorer performance, particularly in tests on attention (the digit span test), cognitive speed and visual recognition [5]. The following studies included only neurologically healthy, non-demented elderly men.…”
Section: Discussionmentioning
confidence: 99%
“…In magnetic resonance imaging studies, subcortical white matter lesions are related mainly to impairment in psychomotor speed, verbal fluency and attention [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Mungas studied the MRI predictors of cognition in patients recruited from academic dementia centres and found that WML were weakly associated with measures of executive function [42]. Similarly, both Amar and Skoog showed in separate studies that WML in patients with dementia adversely affected performance on neuro-psychological testing [43,44]. Conversely, Steingart, in his early study on cognitive and neurologic Wndings in Alzheimer patients with WML, failed to show an association between poor psychometric performance and WML after adjusting for the effects of age, sex, education and the presence of cerebral infarctions [45].…”
Section: Discussionmentioning
confidence: 97%